Efeito agudo de diferentes estratégias de aquecimento no desempenho das corridas de média e longa distância - Alves, Micael Deivison de Jesus (2023)
Introduction: The influence of warm-up as an ergogenic strategy has been widely studied. However, the effects of intensity and different protocols applied in medium and long-distance runners still remain inconclusive. Purpose: To verify the acute effect of active warm-up on middle and long-distance running performance. Methods: This study used two investigations: 1) The systematic review was conducted in PubMed, SPORTDiscus, Scopus and Web of Science databases. Studies were included that investigated possible acute effects of warm-up on exhaustion test (TTE) or time trial (TT) performance in middle- and long-distance runners. 2) Randomized crossover study with the participation of thirteen longdistance runners (34 ± 10 years, 62 ± 6 kg, distance in Cooper Test 3311 ± 245 meters). The athletes performed two 5000 m time trials, preceded by two warm-up conditions, separated by 72 hours of recovery. A standard warm-up of 500 m continuous run (70% of the Cooper Test), followed by two warm-up protocols: high intensity: 3×250 m (100% of the Cooper Test) or low intensity: 3×250 m (70% of the Cooper Test). Countermovement Jump (CMJ), rating of perceived exertion (RPE), blood lactate concentration (BLa) tests were applied, and running performance in the 5000 m TT was quantified. The T-test for dependent samples was used to compare the final time in TT, RPE, and internal session load (ILS). Then, two-way repeated measures analysis (ANOVA), was performed to check the effect of time and condition, followed by Bonferroni post hoc. Results: 1) The systematic review included 31 studies. In 42% of the studies there was improvement and in 12% detrimental effects on performance. The protocols effective on performance were characterized by combining continuous running and/or moderate to high intensity sprints, and adding drop jump, mobility exercises, static stretching or breathing, weighted or cooling vests, or thigh cooling packs. On the other hand, isolated static stretching protocols were the most detrimental to performance. Running distances ≥3200 m was improved between 1-5.7%, shorter distances had improvements between 1-5.9%, and in TE the improvement was between 2.9-15.4%. However, detrimental effects on performance occurred between 3.3-24.5%. Furthermore, transition period ≥15 min was present in the effective protocols. 2) In the original study, better performance was observed in the 5000 m CR after high intensity warmup when compared to low intensity warm-up (1141.4 ± 110.4 s vs. 1147.8 ± 111.0 s; p = 0.03; Hedges' g = 0.66). CMJ was improved after the high intensity warm-up (pre vs. post warm-up) (p = 0.008). Post-warm-up BLa was higher in the experimental condition (3.5 ± 1.0 vs. 2.3 ± 1.0 mmol/l; p = 0.02), similar results for RPE (p = 0.002) and ILS (p = 0.03). Conclusion: Continuous running and/or sprints of moderate to high intensity alone or combined with other ergogenic strategies promote improvement in middle- and long-distance running. We evidenced that performance in the 5000 m TT improved after a warm-up structured by high-intensity sprints. The transition period ≥15 min showed greater effectiveness in recovery and performance enhancement.